Exploring the Relationship of Thalassemia Major and Gingival Health: A Narrative Review - Ruaa Riyadh Al-Hamdani; Maha Shukri Mahmood (مجلة الكوفة الطبية)
Background: Periodontal disease is characterized by the inflammation of the tooth’s supporting tissues, and its etiology is multifactorial. Defense against pathogens depends on the host's immune response, since both innate and adaptive immune cells contribute by releasing their substances and modes of action to preserve harmony in periodontal tissues. Bacterial persistence and immune system dysregulation, characterized by an exaggerated response, can exacerbate periodontal disease. Thalassemia major is an autosomal recessive genetic disorder caused by a mutation in the gene responsible for the β-globin component of the hemoglobin molecule, resulting in either absent or reduced synthesis of this protein in erythroid cells. Individuals with thalassemia major exhibit significant immunological impairments, increasing susceptibility to infectious and inflammatory conditions. The current review aims to explore the relationship between this systemic disease and its effect on the gingival health. The details about gingival health and disease, as well as thalassemia major-associated complications and therapy, have been discussed in this review.  Conclusion: Patients with thalassemia major exhibit a greater likelihood of gingival inflammation compared to systemically healthy individuals.